Oropharyngeal cancer and human papillomavirus: a visualization based on bibliometric analysis and topic modeling - Liu, Zhu; Wang, Haixu; Xu, Yang; Wei, Hongming; Zhang, Yuchong; Dong, Huilei (Frontiers in Microbiology, 2024)
The incidence of oropharyngeal cancer (OPC) is increasing. This study used bibliometric analysis and topic modeling to explore the research trends and advancements in this disease over the past ten years, providing valuable insights to guide future investigations. Methods: 7,355 English articles from 2013-2022 were retrieved from the Web of Science Core Collection for bibliometric analysis. Topic modeling was applied to 1,681 articles from high-impact journals, followed by an assessment of topic significance ranking (TSR). Medical Subject Headings (MeSH) terms were extracted using R and Python, followed by an analysis of the terms associated with each topic and on an annual basis. Additionally, genes were extracted and the number of genes appearing each year and the newly emerged genes were counted.The bibliometric analysis suggested that the United States and several European countries hold pivotal positions in research. Current research is focused on refining treatments, staging and stratification. Topic modeling revealed 12 topics, emphasizing human papillomavirus (HPV) and side effect reduction. MeSH analysis revealed a growing emphasis on prognosis and quality of life. No new MeSH terms emerged after 2018, suggesting that the existing terms have covered most of the core concepts within the field of oropharyngeal cancers. Gene analysis identified TP53 and EGFR as the most extensively studied genes, with no novel genes discovered after 2019.However, CD69 and CXCL9 emerged as new genes of interest in 2019, reflecting recent research trends and directions.HPV-positive oropharyngeal cancer research, particularly treatment deescalation, has gained significant attention. However, there are still challenges in diagnosis and treatment that need to be addressed. In the future, more research will focus on this issue, indicating that this field still holds potential as a research hotspot.